EFFECT OF INCLUSIVE EDUCATION ON THE PERFORMANCE OF STUDENTS IN MATHEMATICS AND ENGLISH LANGUAGE: A SCHOOL STUDY - Agunloye, Olajide O.; Smith, Betty R. (European Scientific Journal, ESJ, 2015)
Inclusion, as a model for educating students with disabilities (SWDs) is a fairly recent phenomenon that is changing the face of instructional settings and formats in schools in the United States. Inclusion is achieved through the seamless collaborative efforts of both general education and special education teachers in inclusive instructional settings. The purpose of this study is to determine the effect of inclusion, as an instructional practice, on the performance of students in a middle school in Southern, USA. The study covers a two-year period for groups of 5th grade students in mathematics and English Language Arts (ELA), in inclusive and general education instructional settings, through to the time they completed 6th grade. Data on the performance of the students in inclusion classes, in mathematics and ELA, over the two year period, were collected and analyzed. The concern that the performance needs of the special education students are not being met in the inclusion settings, and that the setting may be detrimental to the performance of regular education students, is not supported by the findings of this study in the two content areas. Implications for instructional leadership are also examined.